2018
DOI: 10.1038/s41567-018-0070-7
|View full text |Cite|
|
Sign up to set email alerts
|

Quantum Landauer erasure with a molecular nanomagnet

Abstract: The erasure of a bit of information is an irreversible operation whose minimal entropy production of k B ln 2 is set by the Landauer limit 1 . This limit has been verified in a variety of classical systems, including particles in traps 2,3 and nanomagnets 4 . Here, we extend it to the quantum realm by using a crystal of molecular nanomagnets as a quantum spin memory and showing that its erasure is still governed by the Landauer principle. In contrast to classical systems, maximal energy efficiency is achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
80
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 26 publications
9
80
0
2
Order By: Relevance
“…Hence, in these regions neither bound is any more informative than Clausius' law, Eq. (8). Notice that a lower environmental temperature reduces the size of these regions significantly, and we remark for β 10 we find β Q > 0 (since the environment is essentially in its ground state) and one bound is always positive.…”
Section: B Tightness Of the Boundsmentioning
confidence: 50%
See 2 more Smart Citations
“…Hence, in these regions neither bound is any more informative than Clausius' law, Eq. (8). Notice that a lower environmental temperature reduces the size of these regions significantly, and we remark for β 10 we find β Q > 0 (since the environment is essentially in its ground state) and one bound is always positive.…”
Section: B Tightness Of the Boundsmentioning
confidence: 50%
“…(2) as the "entropic bound". The growing interest in exploring the thermodynamics of quantum systems [3] has led to a closer examination of Landauer's principle and the dissipated heat [6][7][8][9][10][11][12][13][14][18][19][20][21]. Recently, a different approach to bounding β Q was proposed in Ref.…”
Section: Arxiv:170709266v2 [Quant-ph] 13 Oct 2017mentioning
confidence: 99%
See 1 more Smart Citation
“…
Finite-size spin systems could constitute key elements in future spintronics devices [1][2][3][4][5], longlasting nano-scale memories [6] or scalable and noise-resilient quantum computing platforms [7][8][9]. They are also natural test-beds for investigating peculiar quantum phenomena [10]. Inelastic Neutron Scattering is the technique of choice to model these systems.
…”
mentioning
confidence: 99%
“…Recently, however, it was demonstrated that carefully built artificial systems can actually operate very close to the Landauer's bound. This was achieved with several types of systems: a single colloidal particle in an optical 14,15 or feedback [16][17][18] traps, nanomagnetic bits [19][20][21] , superconducting flux bit 22 and even quantum systems 23,24 . Based on these results, it is natural to ask whether there are any biological memory erasing processes that operate close to the Landauer's limit.…”
Section: Introductionmentioning
confidence: 99%